ASPEK NATURE OF SCIENCE DALAM BUKU TEKS IPA SMP KELAS IX - Nurul Amaliyah; Erman Erman (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
One of the attempts that science as the subject should address is to promote students’ scientific literacy by embedding the nature of science (NOS) into science textbooks as one of the primary resources in learning. This research aimed to describe the NOS aspects presented within the three science textbooks in grade 9. This study used a descriptive research method to describe the ten aspects of NOS adopted from Abd-El-Khalick et al. (2008). Data were collected by quoting every sentence or paragraph regarding each targeted NOS aspect and later were grouped and analyzed descriptively to describe the completeness of ten aspects of NOS. Analyses showed that NOS indicators did not completely address the targeted NOS aspects within the three science textbooks. Textbook A addressed seven out of ten aspects of NOS, the highest among the other two, whereas Textbook B and Textbook C did only five and six. NOS aspects most addressed within the three textbooks were empirical, scientific theories, and social and cultural embeddedness of science. Some of the targeted NOS aspects, inferential, creative, and scientific methods, were not addressed within the three science textbooks. The inadequacy of targeted NOS aspects within the textbooks was believed to be related to authors’ and publishers’ interests regarding NOS. The inadequacy of targeted NOS aspects would lead to insufficient NOS learning in the classroom, and science literacy as the primary goal in science learning would be difficult to achieve.